Combustion ash residue management an engineering perspective - Goodwin, Richard W. (William Andrew, 2014)
Combustion Ash and Residue Management assists owners and operators of Coal-fired and Resource Recovery Power Plants. By applying the principles and reviewing the case studies examples described within this book, accidents and upsets can be avoided and regulatory permitting can be achieved - reducing costs. This unique book is an essential reference for anybody responsible for disposal or utilization of combustion residues. It reflects over 30 years of engineering practice, applying the principles of concrete chemistry and civil engineering/soil mechanics as confirmed by field data. Dr. Richard Goodwin assesses the composition and environmental impact of combustion residues, and provides not only best practices for safe disposal, but also a blueprint for effective reuse, including applications like structural fill, grout, and capping material. Case studies and cost information for ash disposal options are included, in addition to the lessons learned by high-profile failures, such as the TVA Kingston fossil plant coal fly ash slurry spill in 2008. It also applies engineering principles to discuss how to avoid future upsets, including better operator training and monitoring methods. A comprehensive update to reflect changes in legislation and practice, including new material on the safe disposal or beneficial use of coal ash. A straightforward engineering approach, providing practical guidance and field data--Written by an established expert in the field.